Impact of introduction of crafts with outboardengines on marine fish production in Kerala andKarnataka – a study through Intervention analysis. - Sathianandan, T V; Kuriakose, Somy; Mini, K K; T V, Joji (Indian Journal of Fisheries, 2014)
In the recent years, the contribution from outboard sector is a major componentin the total marine fish production from the states of Kerala and Karnataka.This is as a result of the introduction of crafts fitted with outboard engines forpropulsion in the mid eighties, which intensified and developed into a majorsector. The impact of this intervention is examined here by adopting two populartime series methods used for intervention analysis. The first method is based onseasonal ARIMA modeling and the second is based on regression modeling withARMA type errors. Quarterwise total marine fish landings in the two statesduring 1960-2000 were used for the impact study. The analysis revealed thatfor Kerala the model found suitable is seasonal ARIMA type model and forKarnataka the feasible model was regression model with ARMA errors. Basedon the final estimated intervention models, the effect of the interventions wasestimateds as 2.26 lakh tonnes and 88 thousand tonnes per annum respectivelyfor Kerala and Karnataka.